PENGARUH KESADARAN HUKUM MAHASISWA UNIVERSITAS TANJUNGPURA DI KOTA PONTIANAK TERHADAP PEMBELIAN AKUN NETFLIX MELALUI PENJUALAN NON RESMI - NIM. A1012201081, WINDA NASYWA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac The development of the globalization era has brought numerous changes in various aspects, one of which is the emergence of streaming services that leverage the large number of internet users. Netflix, as a streaming service popular among the younger generation, is certainly accompanied by various issues, including illegal activities such as the sale of Netflix streaming packages by unofficial sellers. This research is conducted to assess the level of legal awareness influencing the decisions of students at Tanjungpura University in Pontianak who have previously engaged in purchasing Netflix services from unofficial sellers.This study employs an empirical juridical approach by understanding social phenomena occurring in society through the distribution of questionnaires to observe the implementation of law within the community. The obtained data are analyzed using thematic analysis techniques, specifically through the identification and analysis of respondent answers.The results indicate the impact of legal awareness on the decision-making process of students regarding the purchase of Netflix accounts through unofficial sellers. It is shown that 50% of respondents are aware of Netflix